Pengaruh Online Promotion Terhadap Keputusan Pembelian - Lu’lu Ul Maknunah; Anwar Hakim Darajat; Nesya Ivanda Putri (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the effect of the independent variable (online promotion) on the dependent variable (purchase decision). A questionnaire was distributed to 40 customers of Salon Rumah Cantik Selorejo, Blitar Regency. The results, tested using statistical tests, show that the data passed both the normality test and the heteroscedasticity test. The conclusion drawn from this study is that the independent variable (online promotion) has a significant positive effect on the dependent variable (purchase decision), as evidenced by the sig. value in the coefficients table being greater than 0.05.